Establishment and application value of a novel prescription medication abuse monitoring model for psychiatric hospitals - Du, Zhiqiang; Jiang, Ying; Lu, Rongrong; Shen, Yuan; Ou, Mengmeng; Wang, Zhe; Cao, Lina; Zhou, Qin; Zhu, Haohao (Frontiers in Psychiatry, 2023)
Objective: To construct a prescription medication abuse (PMA) monitoring model for psychiatric hospitals and to assess its applicability. Methods: A PMA monitoring working group was established to guide the formulation of a PMA monitoring system, which included three active real-time monitoring modes and one retrospective analysis monitoring mode. The effect of the established system was analyzed. Results: In 2021, 35 cases of effective PMA were reported, which was a significant increase compared to 2 cases identified through passive monitoring mode in the preceding year. Most of the reported cases were based on active real-time monitoring mode. Among them, 21 cases (60.00%) were identified during the diagnosis and treatment of medicine and nursing; 3 cases (8.57%) were reported based on drug concentration detection technology; 5 cases (14.29%) were reported by the laboratory department during PMA screening. Besides, 6 cases (17.14%) were reported according to the retrospective analysis of the hospital information system. The majority of prescription medication abusers were adolescents under the age of 18 (12 cases, 34.29%). Overall, there were 27 cases of class II psychotropic prescription medications, accounting for 77.14%. Conclusion: The combined PMA monitoring model can effectively improve the quality of PMA monitor and provide a basis for the supervision for higher-level regulatory authorities.